Manejo de residuos sólidos municipales en la localidad de Habana 2010 - Chuquirima Paladines, Yakelin (2012)
The present thesis project seeks to improve the solid waste management system in those cities and towns with rural skills, and those that is in the process of urban consolidation as is the case at hand, in the Habana town, the same who belongs to the Moyobamba province , San Martin department - Peru. In this regard I put in the possession of the municipality of the Habana district a modest study on the management of municipal solid waste, the same that are generated in both urban and periurban part of the town. In this project we offer information on: - Determination of the production and physical composition of the solid residues citizens generated; - I diagnose of the current situation of the solid municipal residues; - Determination of the existing problems and the environmental impacts that there causes the lack of a managing of the solid municipal residues; - Offer of measures and / or actions for the suitable improvement of the system of managing of solid municipal residues in the Habana locality. It is important to know that the production per-capita in the Habana city is of 0.691 kg/hab /day, with a density of 244.45 kg/m3. As for his physical composition, there was obtained that the component organic matter represents 75.99 % of the total of residues; with regard to the recyclable material there is had a total of 4.2 % of rigid plastic (unimportant bottles, etc.), followed by tins with 3.74 %, the not rigid plastic represents (bags) 3.18 %, the paper (white paper, periodic paper and paper I file) and the carton represent 2.22 %, the glass represents 1.25 %. To finish first in this context I am pleased to have culminated with the overall aim of developing a "Proposal of measures and/or actions for the Improvement of the system of Municipal Solid Waste Management in the Habana town “, which seeks to improve and contribute to the harmonious development and healthy of this small ecosystem located in this part of the San Martin Region, 2010